IMPLEMENTASI LAPOR KAND4 (KELOLA ADUAN NASIHAT DITINDAKLANJUTI AGAR TUNTAS) KABUPATEN PROBOLINGGO - Verto Septiandika; Nourma Ulva Kumala Devi; Alisyia Putri Melani; Mahfudz Jailani Aminulloh (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2025)
The Regional Government with the Communication, Informatics, Statistics and Cryptography Service of Probolinggo Regency launched an innovative program, namely Lapor KAND4 (Manage Advice Complaints Followed Up to Be Completed). This program aims to facilitate residents in reporting problems in an easy way, namely by sending short messages via the WhatsApp application. This program can be contacted by all residents of Probolinggo Regency at 082-131-001-001. This research uses a qualitative method with a descriptive approach. Qualitative research focuses on complexity, social context and data collected naturally or directly from the source without manipulation. Descriptive techniques involve collecting and analyzing data to describe the quality of the nature or pattern that exists in the phenomenon being studied. In this research, the topic selection was on the Implementation of Lapor KAND4 (Manage Advice Complaints Followed Up to Be Completed) of Probolinggo Regency. Focusing on research on the implementation of the Lapor KAND4 program managed by the Communication, Informatics, Statistics and Cryptography Service of Probolinggo Regency. This is adjusted to the use of the Public Policy Implementation theory according to Thomas B. Smith.